Hemoparasites of the genus Trypanosoma (Kinetoplastida: Trypanosomatidae) and hemogregarines in Anurans of the São Paulo and Mato Grosso do Sul States - Brazil - Leal, Denise D. M. [UNESP]; O'dwyer, Lucia H. [UNESP]; Ribeiro, Vitor C.; Silva, Reinaldo J. [UNESP]; Ferreira, Vanda L.; Rodrigues, Rozangela B. (Academia Brasileira de Ciências, 2009)
Os animais silvestres estão expostos a inúmeros patógenos,dentre eles estão os hemoparasitas. Podem-se destacar espécies do gênero Trypanosoma e do grupo das hemogregarinas,que ocorrem com freqüência parasitando anuros (rãs, pererecas e sapos). Normalmente, a descrição destes hemoparasitas é feita através da morfologia dos estágios observados nosangue periférico do hospedeiro e as pesquisas sobre o ciclobiológico desses hemoparasitas são escassas. Os objetivos dopresente estudo foram avaliar a presença de hemogregarinas eTrypanosoma spp. em anuros capturados nos Estados de São Paulo e Mato Grosso do Sul e fazer a caracterização morfológica e morfométrica dos seus hemoparasitas. As espécies deanuros examinadas foram: Dendropsophus nanus, D. minutus, Leptodactylus chaquensis, L. podicipinus, L. labyrinthicus, L. fuscus, Bufo granulosus, B. schneideri, Phyllomedusahypocondrialis, Trachicephalus venulosus, Scinax fuscovarius e Hypsiboas albopunctatus. Dos 40 animais estudados, foramencontrados quatro (10%) positivos para hemogregarinas e oito(20%) positivos para Trypanosoma spp. Foram observadosgamontes de hemogregarinas com morfologia variável e, alémdas formas intraeritrocíticas, também foram observados gamontes fora das hemácias. As formas de Trypanosoma encontradas eram muito polimórficas, conforme é descrito na literatura, sendo na sua maioria, larga e oval.

Wild animals are exposed to numerous pathogens, including hemoparasites. The Trypanosoma and hemogregarinegroup are frequently reported as parasites in anurans (frogs, tree frogs and toads). The identification of these hemoparasites is usually made through stage observation of their morphology in the peripheral blood of the host. There areno studies, however, based on the biological cycle of these hemoparasites. The objective of the present study was toevaluate the presence of hemogregarines and Trypanosoma spp. in anurans captured in the States of São Paulo andMato Grosso do Sul- Brazil and to perform the morphological and morphometric characterization of these hemoparasites. The species of anurans examined were: Dendropsophus nanus, D. minutus, Leptodactylus chaquensis L. podicipinus, L. labyrinthicus, L. fuscus, Bufo granulosus, B. schneideri, Phyllomedusa hypocondrialis, Trachicephalus venulosus, Scinax fuscovarius and Hypsiboas albopunctatus. of the total of 40 animals studied, four (10%)were positive for hemogregarines and eight (20%) were positive for Trypanosoma spp. Hemogregarine gamontsshowed variable morphology and, in addition to intraerythrocytic forms, extraerythrocytic forms were also observed.Extremely different forms of Trypanosoma were observed, as described in the literature, with the broad and oval forms being the most common.
Keywords: Anuros; hemogregarinas; Trypanosoma; hemoparasitas; Anuran; hemogregarine; Trypanosoma; hemoparasites